A brilliant blend: a socially diverse solution to the employment paradigm of the Western Australian restaurant industry and the impacts of enacted change - Higgins, Catherine; Howe, Christina; Taylor, Ruth (School of Management, University of South Australia, 2011)
The Western Australian economy is booming as a consequence of a resurging mining industry. A severe lack of prospective employees and skills shortages, however, has resulted in significant competition for entry level staff across many industries. The labour intensive restaurant industry has long utilised marginalised employees and is now reliant on secondary labour markets to meet its human resource requirements. The industry, predisposed to domestic students as employees, is now increasingly reliant on the more marginal employee cohort of international students. This research paper is an exploratory study investigating the value of international students as a reliable source of labour for the Western Australian restaurant industry as perceived by industry employers and industry representatives inclusive of Hospitality Training Providers, the Australian Hotels Association (Western Australia) and the Restaurant and Catering Association. Findings from the respondents suggested that should delinking student visas from permanent migration status occur, the number of international students intending to study in Australia will reduce considerably resulting in reduced numbers of international students available to be employed by the restaurant industry. Respondents further believed that diminishing international student numbers would further labour shortages resulting in unmet customer expectations, increased food and beverage costs and shrinkage to both restaurants individually and the Western Australian restaurant industry as a whole.